2016
DOI: 10.1016/j.giq.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Governance and innovation in public sector services: The case of the digital library

Abstract: This paper examines the co-evolution of public governance and innovation, and proposes an adaptation of\ud Hartley's model to take into consideration such co-evolution. This model is then applied to a longitudinal case\ud study of the digitalization of Roskilde University Library. The theoretical and empirical analysis yields four\ud main results. First, it is shown that the transition froma NewPublic Management approach towards a Networked\ud Governance mode implies a greater distribution of knowledge and inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 33 publications
0
56
0
6
Order By: Relevance
“…Arranging the governance of these teams are challenging and it is found that public governance and innovation co-evolve (Scupola and Zanfei 2016). A greater distribution of knowledge and innovation across different organizational levels within public administrations is to be found necessary (Scupola and Zanfei 2016).…”
Section: Organizing Data-driven Innovationmentioning
confidence: 99%
“…Arranging the governance of these teams are challenging and it is found that public governance and innovation co-evolve (Scupola and Zanfei 2016). A greater distribution of knowledge and innovation across different organizational levels within public administrations is to be found necessary (Scupola and Zanfei 2016).…”
Section: Organizing Data-driven Innovationmentioning
confidence: 99%
“…Understanding and managing innovation are one issue most widely in the contemporary public administration (Osborne & Brown, 2011;Torfing & Triantafillou, 2016). Thus, governance innovation seems very diff erent from innovations in products, services, and processes (Moore & Hartley, 2008;Antt iroiko, Bailey, & Valkama, 2011;Scupola & Zanfei, 2016). Governance innovation can promote innovation capacity from the public sector, arguing that it is oft en viewed as an alternative but should view as complementary.…”
Section: Resultsmentioning
confidence: 99%
“…The other side, innovation also needs to be well managed for such innovations can show the benefi ts. Scupola and Zanfei (2016) in his investigation revealed that governance innovation requires user participation to achieve greater inclusiveness. Although the governance theory rare in the innovation literature (Moore & Hartley, 2008), the researchers can learn to governance innovation from concept and approach of innovation and governance contextually (Antt iroiko, Bailey, & Valkama, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Empathy implies the ability of the human resources, in this case, woman workers, to serve and be able to see things or problems from the community's point of view. It added with any profitable activity in a public organization which is not merely a physical product, but how to satisfy the community that has been served by the employees (Scupola & Zanfei, 2016). Women employees are naturally more empathetic than men and more patience in providing services to the community so that they can provide a great quality of services (Seguino, 2000).…”
Section: The Performance Of the Female Employees In Public Servicementioning
confidence: 99%